ANALISIS KEBIJAKAN PENGELOLAAN SAMPAH DI KABUPATEN BANYUMAS - Farih Rizqi Putranto; Tri Yuniningsih; Ida Hayu Dwimawanti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Policies are always attached to every state life. A good policy is one that is able to solve problems carefully, including in waste management policies. The more the human population, the greater the amount of waste produced and if it cannot be managed properly, the problems will be more complex. The waste management policy in Banyumas Regency has yet to find a concrete solution to the waste problem both from the generation and follow-up problems. This research is an analysis of waste management policies in Banyumas Regency with the aim of analyzing and recommending policy alternatives. This research uses a qualitative descriptive method with snowball sampling technique in determining informants with the key informant being the Head of the Banyumas Regency Environmental Service. The theory used is the theory of policy analysis from Bardach (in Tumanggor, 2018), namely finding problem formulations, determining goals and objectives, identifying policy parameters, seeking policy alternatives, assessing policy alternatives, and recommending policies. The selected policy parameters in determining the assessment of alternative policies use Patton Sawicky's criteria (in Yuniningsih, 2015), namely technical feasibility, economic and financial capability, political feasibility, and administrative capability. Adequate TPST, lack of community commitment, and failure of waste management policies to meet targets. This study recommends that the Government of Banyumas Regency conduct outreach to the community regarding source-based waste management and recommends that the policy needed is the development of hangars and TPST at the sub-district level as a source-based waste management method.